Nurse-led interventions for cervical cancer patients: A scoping review with an emphasis on East Asian contexts - Olabisi Fatimo Ibitoye; Joshua Kanaabi Muliira; Eilean Rathinasamy Lazarus; Jane Frances Anyango; Gerald Amandu Matua (Belitung Nursing Journal, 2026)
Background: Nurse-led interventions play a vital role in cervical cancer care across the disease trajectory but are often underappreciated despite their impact on patient-reported outcomes. Objective: This review aimed to map current nurse‑led interventions for women with cervical cancer across the disease trajectory, identify key design gaps, reporting, and evaluation to guide practice and research Methods: The scoping review was guided by Arksey and O’Malley’s framework for conducting scoping studies. The included studies were published between 2015 and 2025 and were identified through searches of MEDLINE, Scopus, Embase, CINAHL, and ScienceDirect. The final database search was conducted on 31 December 2025. The studies were empirical studies on nurse-led interventions targeting management of cervical cancer patients. The primary results were organized by themes using a line-by-line coding method. Results: Of the 1,220 studies identified, twenty-two met the inclusion criteria. Most studies used quasi-experimental designs, with few randomized, mixed-methods, or qualitative studies. The nurse-led interventions emphasized health education and psychological support, and improved sexual function, mental health, disease knowledge, quality of life, self-efficacy, personal confidence, and body image. Important elements of cervical cancer care such as cost of care, financial burden, palliative and end-of-life care, and cancer recurrence were mostly not addressed by any intervention. Conclusion: The included studies frequently reported positive outcomes associated with nurse-led interventions such as improved patients’ sexual function, quality of life, mental health, emotional well-being, family functioning, symptom burden, self-management, knowledge, and satisfaction with care. Registry: PROSPERO [CRD420261277487]